Classroom's climate and good teaching methods with vulnerable teenagers: further from academic contents - Marco Antonio Manota Sánchez; Miguel Melendro Estefanía (Universidad de La Rioja, 2015)
The aim of this article is to analyse a series of elements related with good teaching practices, which are of remarkable importance in the configuration of the classroom climate, especially regarding vulnerable students. We start from the perception of teachers, tutors and students from first cycle of secondary education contrasted with three instruments: the "Child Multifactorial Adaptation Test" (TAMAI) and two surveys about "Perception of the classroom climate by the students" (PCA-A), and "Perception of the classroom climate by the teachers" (PCA-P). Between obtained results, as good teaching practices in relation with the climate of the classroom, it is pointed out the listening attitude from the teacher towards the alumni, their availability to accompany them on their educative process and neutralise the creation of stereotypes and excluding labels, the importance of the formation of the teachers in the emotions management, and above all, their inclination to share those emotions. Other significant results show the uneven necessity of being heard of the students, the "blind spot" of negative misconceptions between teachers and students, and the way that students' perception change depending on their vulnerability degree and the level of failure at adapting to school they might present.